The performance of crossbred dairy calves given different levels of whole milk and weaned at different ages - Khalili, H.; Crosse, S.; Varvikko, T. (Cambridge University Press, 1992)
Forty-five Friesian X Zebu crossbred calves (4 days old) were used to evaluate the effect of feeding different levels of whole milk and weaning at different ages. A total of 252 litre whole milk offered over 12 weeks was compared with a feeding level of 134 litre milk offered over 8 weeks. Water given ad libitum was also compared with allowing access to water once daily. The calves were penned and fed individually. Average daily gain of calves weaned at 12 weeks was greater compared with calves weaned at 8 weeks of age and allowed access to water once daily and with calves weaned at 8 weeks and given water ad libitum. Feeding extra milk and weaning at 12 weeks decreased the intake of concentrates and increased live-weight gain.